2018
DOI: 10.1097/olq.0000000000000756
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Detection of Trichomonas vaginalis in HIV-Infected Pregnant Women

Abstract: Culture was positive in roughly half of PCR-positive cases. The culture-negative cases had significantly higher Ct values, indicating a lower concentration of T. vaginalis DNA. A Ct value of 30 provides a reliable threshold for predicting culture positivity. The clinical significance of culture-negative infections detected by PCR is still unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…However, we previously reported on a sub-study involving TV culture in a subset of women with persistent positive TV results. 32 In that study we found that 50% of participants with a positive test-of-cure results had viable organisms. That study also found that test-of-cure PCR cycle threshold value from test-of-cure specimens was predictive of T. vaginalis culture positivity, and thus viable infection.…”
Section: Discussionmentioning
confidence: 84%
“…However, we previously reported on a sub-study involving TV culture in a subset of women with persistent positive TV results. 32 In that study we found that 50% of participants with a positive test-of-cure results had viable organisms. That study also found that test-of-cure PCR cycle threshold value from test-of-cure specimens was predictive of T. vaginalis culture positivity, and thus viable infection.…”
Section: Discussionmentioning
confidence: 84%
“…With the advent of AIDS, all STI have assumed great importance in the context of public health, since all are considered as facilitators of HIV infection [4]. Thus, new strategies that increase STI screening coverage are needed globally.…”
Section: Discussionmentioning
confidence: 99%
“…In order to reduce adverse health effects, in particular the facilitation of HIV acquisition and transmission and undesirable clinical outcomes in pregnancy and perinatal morbidity [3][4][5], the combination of self-collection coupled with the rapid immunochromatographic test for T. vaginalis would be an ideal combination when utilized in remote areas such as riverside communities. The woman would apply the self-sampling in a private setting, take the test, have the result quickly, and receive the medication, going well beyond the syndromic approach [31].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations